Examination of fingerprint image quality and performance on force acquisition vis-à-vis auto-capture - Senjaya, Benny; Elliott, Stephen; Modi, Shimon; Tae Bong Lee (44th Annual 2010 IEEE International Carnahan Conference on Security Technology, 2010)
The purpose of this paper was to provide additional information about the use of force in a fingerprint recognition system. Instead of looking just at the relationship between force and performance, this paper examines not only that relationship, but also examines image quality, biometric sub-system processing time, as well as subjects comfort levels. The results of this paper show that for this particular commercially available fingerprint sensor, the force level needed for optimal performance, image quality and comfort is approximately 5.5 N.